Latest Advances in Preservation Technology for Fresh Fruit and Vegetables - Jin, Peng (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Fresh fruit and vegetables are considered as essential components of a healthy human diet, due to their pleasant taste and rich nutrients. However, fruits and vegetables are characterized by production seasonality, regionality, and perishability, which greatly affect the acceptance of consumers and increase the challenges of their post-harvest storage and preservation. A plurality of preservation technologies, including chemical treatment (calcium chloride, 1-methylcyclopropene, salicylic acid, etc.), physical methods (low-temperature conditioning, controlled atmosphere storage, ultraviolet-C irradiation, etc.), and biotechnology (such as genetic engineering technology) have been applied to maintain storage quality and to extend the storage life of fresh fruit and vegetables in recent years. Developing advanced preservation techniques to prolong the storage life of fruit and vegetables is of importance for improving social and economic benefits. Therefore, we invited authors to contribute original research articles and review articles focused on the innovative preservation technology of fresh produce, addressing storage problems, such as post-harvest quality deterioration caused by senescence, physiological disorders, and disease, to extend the shelf-life of fresh produce and reduce post-harvest loss.